Criminal Woman, the Prostitute, and the Normal Woman - Lombroso, Cesare (Duke University Press, 2004)
Frontmatter -- Contents -- List of tables -- List of illustrations -- Acknowledgments -- Editors’ Introduction -- Author’s Preface -- PART I. The Normal Woman -- 1 The Female in the Animal World -- 2 Anatomy and Biology of Woman -- 3 Senses and Psyche of Woman -- 4 Cruelty, Compassion, and Maternity -- 5 Love -- 6 The Moral Sense -- 7 Intelligence -- PART II. Female Criminology -- 8 Crime in the Animal World -- 9 Crimes of Savage and Primitive Women -- 10 The History of Prostitution -- PART III. Pathological Anatomy and Anthropometry of Criminal Woman and the Prostitute -- 11 The Skull of the Female Offender -- 12 Pathological Anomalies -- 13 The Brains of Female Criminals and Prostitutes -- 14 Anthropometry of Female Criminals -- 15 Facial and Cephalic Anomalies of Female Criminals and Prostitutes -- 16 Other Anomalies -- 17 Photographs of Criminals and Prostitutes -- 18 The Criminal Type in Women and Its Atavistic Origin -- 19 Tattoos -- PART IV. Biology and Psychology of Female Criminals and Prostitutes -- 20 Menstruation, Fecundity, Vitality, Strength, and Reflexes -- 21 Acuteness of Sense and Vision -- 22 Sexual Sensitivity (Lesbianism and Sexual Psychopathy) -- 23 The Female Born Criminal -- 24 Occasional Criminals -- 25 Crimes of Passion -- 26 Suicides -- 27 The Born Prostitute -- 28 The Occasional Prostitute -- 29 Insane Criminals -- 30 Epileptic Criminals and the Morally Insane -- 31 Hysterical Criminals -- Appendix 1: Comparing Three Editions of La donna delinquente -- Appendix 2: Illustrations in the Earlier Editions -- Notes -- Glossary -- References -- Index